Deepening financial inclusion in Nigeria through Islamic Financial offerings - Akosile, Tesleem Olajuwon Isa; Mohd. Zain, Nor Razinah (Springer Nature Switzerland AG, 2023)
This research examines the adequacy of financial inclusion in the northwest and northeast of Nigeria and the role of Islamic finance in deepening financial inclusion in those identified regions. By adopting qualitative analysis, content analysis is used to determine the status of financial inclusion in Nigeria. The study relies on secondary data collected from official documents, working papers, articles, e-books, relevant websites, and online resources. From this study, it is found that providing all necessary access to financial products and services to all members of Nigerian society is important for financial inclusion. Such accesses must be done in an efficient, effective and sustainable manner. Based on the findings, it is recommended for Islamic banks in Nigeria to provide more allocations for equity-based Islamic financial contracts in their financing activities. Moreover, it is necessary for the Central Bank of Nigeria (CBN) as the main regulator of banking and finance industry in Nigeria to consider and issue guidelines and regulations that can expand the country’s financial inclusion through Islamic equity-based financial contracts and products.